Rapid Screening and Quantitative Determination of Illegal Phosphodiesterase Type 5 Inhibitors (PDE-5i) in Herbal Dietary Supplements - Thi Oanh Nguyen; Cao-Son Tran; Thi Thu Hang Do; Thi Minh Hoa Nguyen; Quang-Dong Bui; Cao-Tien Bui; Hong-Ngoc Nguyen; Thu-Hien Dang; Viet-Chien Dinh; Thi Anh Huong Nguyen; Thi Hong Hao Le (Journal of Analytical Methods in Chemistry)
Phosphodiesterase type 5 inhibitors (PDE-5i) are the first-line medication for oral erectile dysfunction, which are used according to the prescription of doctors. However, these substances have been found illegally in supplementary foods. The quality and safety of dietary supplements for enhancing male sexual performance have been questioned, raising the need for continual development of analytical methods. Liquid chromatography coupled with high-resolution mass spectrometry has become one of the most effective methods to identify and measure PDE-5i concentration. In this research, we focused on (i) developing and validating an effective screening and quantitation method for more than 53 PDE-5i in ingredients and supplementary products using LC-Q-Exactive after a simple sample extraction and (ii) assessing PDE-5i content in natural-based supplementary products available in Vietnam market. The extraction method used a small amount of organic solvent, which makes it more environmentally friendly (greener). The developed method has a limit of detection of 0.4 mg/kg, a limit of quantitation of 1.2 mg/kg, recoveries from 80 to 110%, and repeatability lower than 15%. Ninety-two herbal supplementary foods and ingredients used for enhancement of male sexual performance available in Vietnamese markets were collected. Fourteen PDE-5i including conventional and novel analogous were detected and measured in eighteen food supplements and two formulation ingredient samples.